Glycosylation of Siglec15 promotes immunoescape and tumor growth - Wang, Yun-Long (Am J Cancer Res, 2021)
Siglec15 is a recently characterized immunosuppressive transmembrane protein, which expresses in various types of solid tumors and promotes cancer development. Several studies reported that Siglec15 is a prognostic biomarker of cancer patients, and targeting Siglec15 may be a promising strategy for cancer therapy. However, the regulation of Siglec15 function remains unclear. Here we show that the immunosuppression activity of Siglec15 is largely modulated by N-glycosylation. Through mass spectrum and site mutation analysis, we identified that Siglec15 was extensively glycosylated at N172 (N173 for mouse) in cancer cells. Meanwhile, Siglec15 N172Q had a similar molecular weight with PNGase-F-treated Siglec15, suggesting N172 as the only one glycosylation residue. In xenograft model, glycosylation deficiency of Siglec15 reduced tumor growth in C57BL/6 mice, but had no impact in nude mice, indicating the requirement of N-glycosylation for immunosuppressive function of Siglec15. Furthermore, colorectal cancer patients with high Siglec15 expression had a poor response to neoadjuvant chemo-radiotherapy and short survival time. Interestingly, removal of N-glycosylation enhances the detection of Siglec15, which may be employed in the prediction of immunotherapy response. Together, our results disclose a pivotal role of glycosylated Siglec15 in tumor immune escape, which may be a therapeutic target for cancer immunotherapy.